DESEMANTIZATION AS THE BASIC PRINCIPLE OF VERBALIZING THE EMOTIVE ORIGIN OF INTERJECTION AND RELATIVE CONSTRUCTIONS - E. V. Yakovleva (Гуманитарные и юридические исследования)
The study presents the analysis of desemantization as the basic principle of expanding interjection and relative constructions in the language system. The article highlights the ways for emergence of emotive overtones in meaning resulting from embedding of both meaningful lexemes and the existing relative constructions in a new non-usual context. The variety of sense structure and wide compatibility recourses serve the base for such kind of embedding.